Development and assessment of azithromycin paediatric suppository formulations - Mollel, Happiness (Rhodes University, Faculty of Pharmacy, Pharmacy, 2006)
The use of the oral route of administration for the treatment of young children with antibiotics can at times be problematic since, factors such as nausea, vomiting, taste and/or smell, in addition to the challenges associated with the administration of suspensions, may contribute to poor patient compliance. In such cases, the use of the rectal route of administration may be appropriate. Therefore, suppositories containing 250 mg azithromycin (AZI) were manufactured and assessed for potential as an antibiotic suppository dosage form. Suppositories, containing AZI dihydrate were manufactured by the fusion method, using different grades of PEG, WitepsolÂ® and SuppocireÂ® bases. The rate and extent of AZI release was evaluated using USP apparatus I, and samples were analyzed using a validated HPLC method. Differences in the rate and extent of AZI release were observed with the greatest amount of AZI being released from PEG formulations. The rate and extent of AZI release from formulations manufactured using fatty bases were influenced by physicochemical properties, such as melting rate and hydroxyl value, of the bases. In addition drug partitioning appeared to favor the lipid phase and had a negative impact on AZI release characteristics. Two different formulation approaches were used in an attempt to increase the rate and extent of AZI release from fatty base formulations. The use of surfactants significantly increased AZI release from formulations manufactured with fatty bases with high hydroxyl values. The use of urea or Povidone K25 in combination with AZI as a physical mixture or solid dispersion did not increase the rate and extent of AZI release from the fatty suppositories, to any significant extent. The mechanism of drug release was evaluated using several mathematical models, including the Higuchi, Korsmeyer- eppas, Zero and, First order models. In addition, in vitro dissolution profiles were characterized by the difference and similarity factors, f1 and f2 and by use of the Gohel similarity factor, Sd. AZI release kinetics were best described by the Higuchi and Korsmeyer-Peppas models and the values of the release exponent, n, revealed that drug release was a consequence of the combined effects of AZI diffusion, rate of melting of the base and partitioning of the drug which can be considered to be anomalous release.
Keywords: Azithromycin; Pediatrics; Clinical pharmacology; Pharmacokinetics; Suppositories; Drugs -- Dosage forms